Finite element modelling of CFRP wrapped concrete specimens subjected to localised axial compression - Abdullah, Jasim Ali (Penerbit Universiti Kebangsaan Malaysia, 2021)
The strengthening and rehabilitation of reinforced concrete structures using Carbon Fibre Reinforced Polymer (CFRP) wrapping is most common. Recently, this method was used in the rehabilitation of deteriorated reinforced concrete columns, the pier of girder bridges and corbels that are subjected to localised axial compression. The numerical simulation which is verified by experimental works minimizes the time and cost to get the internal behaviours of structures. This study is an attempt to numerically investigate the performance of CFRP wrapped concrete specimens subjected to localised compressive loading conditions. The finite element modelling by ABAQUS software was used in the simulation of adopted specimens in this study. The FEM results show good agreement with the experimental data. The performance of adopted specimens and the behaviour of the concrete core and CFRP wrapping were extensively studied. The FEM results indicated that the CFRP wrapping improves the load carrying capacity and increases the dissipation of energy by increasing the deformation capacity and subsequently the wrapped specimens behave more ductile. The fully wrapped cylinder subjected to a smaller area of loading exhibits higher capacity (119%) of exposed specimen, while the wrapped cube subjected to area of loading (size:75 mm) exhibits higher load carrying capacity about(52%) than the exposed cube.